Recent Trend and Outlook of Tourist Accommodations in Spain at Various Scales: The Challenges of Touristification in Andalusian Municipalities - Jesús Ventura-Fernández; Llorenç Quetglas-Llull; Antonio Gavira-Narváez (Tourism and Hospitality)
As a globe leader in tourism, Spain relies on this sector as a key economic pillar, contributing over 12% to its GDP. The hospitality industry has expanded steadily in response to growing demand. In parallel, recent years have witnessed an exponential rise in tourist accommodations, such as privately owned properties repurposed for short-term rentals, largely facilitated by digital platforms. This study explores the evolution and spatial distribution of these accommodations, assessing their share within the overall housing stock across different scales. The focus is on Andalusian municipalities, a region characterized by both its geographical diversity and its significant tourism footprint. This study highlights two primary areas of concentration: the region’s Atlantic and Mediterranean coastlines (most notably the Costa del Sol, centered in Malaga) and internationally renowned heritage cities such as Seville, Granada, and Cordoba. By applying quantitative methods, this research assesses the clustering of tourist accommodations in relation to major cultural landmarks, including several UNESCO World Heritage Sites. The findings provide an analysis of the implications of this trend, shedding light on the challenges and opportunities it presents within the tourism sector, particularly against the backdrop of mounting criticism surrounding the sustainability and socio-economic impacts of this evolving model of tourism.